Great Subject of Propaganda: by the Traces of Post-communist Autobiographies - Mažeikis, Gintautas (Literatūra, 2008)
The article is devoted to analysis of description of propaganda subject in general and in the Soviet Lithuanian literature particularly. Propaganda subject doesnt depend only on the procedure of discoursive interpellation as it was in L. Althusser theories. The article shows how much important was social-body experiences and social-political body activities upon the examples of communist identity history in Soviet Union. For this reason the notions of symbolic sphere (J. Lotman), semiosis (U. Eco), discoursive order (M. Foucault) and symbolical worlds (J. Lacan) are separated and compared. Contemporary theories of psychoanalytic philosophy show meta-literary origin of politically important literary works and semiosis. It means that the sense of sentences of novels and poems were red and understood in dependency of heroic biography of writer, on the correspondent to the contemporary political and material life of political party and changes of political language. Participation in the revolutionary activity, class war, buildings of Soviet reality, II World Wars battles, postwar struggles, resistance to the Post-soviet reevaluation of all values, proletarian origin, sweat and blood were non-literal signs for the trust to literary work. The article shows that literary works of trusted writers were a collective creation and they were a collective semiosis. On the example of Lithuanian poet E. Mieželaitis collective improvement of poems are discussed. The other step in the development of soviet semiosis and symbolical world goes in the modern independent Lithuania. It is developed in autobiographes of soviet writers and soviet cultural leaders. Post-soviet considerations about “Non lost generation” of one of former communist leader L. Šepetys are analyzed in the article.Post-soviet biographies and popularity of the ones are evidence of stability of soviet symbolical world with their social body practices and reading / writing experiences. Analysis of soviet heritage related to the building of soviet man not only in discoursive but also in the body sense presuppose interpretation of their symbolical worlds from sociological or even political / literary anthropology point of view. The success of soviet auto / biographies in Post-soviet period is also sign of openness of modern Lithuanian society to its memory. It opens well-affected opportunities for Post-communist studies without any repressive desovietization of memory.